Improving Student-Alumni Satisfaction and Institutional Image Through Social Media Engagement in Tourism Vocational Higher Education - Roby Darmadi (Eduturisma, 2021)
Advances in information technology and internet service users are increasing rapidly every year. The behavior of social media users exerts a broad influence on various aspects of the business, including higher education being the background to this research. This research aims to analyze the influence of the image of universities and social media engagement on student and alumni satisfaction and the role of social media engagement in increasing student satisfaction. The study used a survey method conducted on 208 students and alumni of one of the vocational tourism colleges in Jakarta who became followers of the campus' officialInstagram account. Data analysis methods use SEM (Structural Equation Model) with the help of Smart-PLS 3software. The results revealed that the image of the college significantly affects social media engagement and student and alumni satisfaction. Social media engagement significantly affects customer satisfaction, and social media engagement is a significant mediator in the relationship between the college's student and alumni satisfaction image. The conclusion of this study has implications for college management to pay attention to campus social media to improve the college's sustainability.